2023
DOI: 10.1186/s12910-023-00938-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect and comparison of training in ethical decision-making through lectures and group discussions on moral reasoning, moral distress and moral sensitivity in nurses: a clinical randomized controlled trial

Abstract: Background Ethical decision‑making and behavior of nurses are major factors that can affect the quality of nursing care. Moral development of nurses to making better ethical decision-making is an essential element for managing the care process. The main aim of this study was to examine and comparison the effect of training in ethical decision-making through lectures and group discussions on nurses’ moral reasoning, moral distress and moral sensitivity. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A literature review reveals limited research on nurses’ ethical decision-making in end-of-life care in Iran over the past decade (2013–2023). While some studies have explored ethical decision-making, such as, Khaghanizadeh’s, et al (2023) investigation of the effect and comparison of training in ethical decision-making through lectures and group discussions on moral reasoning, moral distress and moral sensitivity in nurses [ 21 ] and, Jamshidi’s, et al, study of the effects of an ethical empowerment program on critical care nurses’ ethical decision-making [ 22 ], However, the studies did not employ a comprehensive tool to measure nurses’ ethical decision-making in end-of-life care, which highlights the need for a valid and specific tool to assess the level of nurses’ ethical decision-making in this area.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review reveals limited research on nurses’ ethical decision-making in end-of-life care in Iran over the past decade (2013–2023). While some studies have explored ethical decision-making, such as, Khaghanizadeh’s, et al (2023) investigation of the effect and comparison of training in ethical decision-making through lectures and group discussions on moral reasoning, moral distress and moral sensitivity in nurses [ 21 ] and, Jamshidi’s, et al, study of the effects of an ethical empowerment program on critical care nurses’ ethical decision-making [ 22 ], However, the studies did not employ a comprehensive tool to measure nurses’ ethical decision-making in end-of-life care, which highlights the need for a valid and specific tool to assess the level of nurses’ ethical decision-making in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Crucial conversations are vital to support emerging nurses in the work that they are required to do upon transition to practice. Recent research has indicated that education in ethical decision-making through group discussions is an effective strategy for improving moral reasoning and moral sensitivity in nurses (Khaghanizadeh et al, 2023).…”
mentioning
confidence: 99%